Quality Diets for Better Health (QDBH) - International Potato Center (International Potato Center, 2017)
European Union finances new project addressing malnutrition in Southern Nations, Nationalities and Peoples Region (SNNPR), Ethiopia by combining orange-fleshed sweetpotato with innovative nutrition education and value chain development.